Endovascular Management of Basilar Artery Aneurysms Associated with Fenestrations - Islak, Civan; Kocer, Naci; Kantarci, Fatih; Saatci, Isil; Uzma, Omer; Canbaz, Bulent (American Journal of Neuroradiology, 2002)
BACKGROUND AND PURPOSE: Arterial fenestrations are associated with saccular aneurysms that are often difficult to treat with open surgical techniques. We evaluated our experience with endovascular treatment of such aneurysms.METHODS: Ten consecutive patients with 11 basilar artery aneurysms associated with fenestrations were treated with coils by means of the endovascular route between November 1994 and February 2000. All patients underwent endovascular embolization by the femoral approach, under general anesthesia. Twelve embolization procedures were perfomed in the 10 patients.RESULTS: Nine proximal and two distal basilar artery fenestration aneurysms were treated successfully. The embolization was complete in 10 of the 11 aneurysms. It was incomplete in one case, and complete occlusion could not be achieved at the second attempt. There was one regrowth at 1-year follow-up, which was successfully treated again. Four of the aneurysms were treated initially with balloon remodeling, whereas one aneurysm with regrowth and one with incomplete occlusion were treated with balloon remodeling at the second embolization procedure. In one case, one limb of the fenestration was sacrificed.CONCLUSION: Endovascular treatment of basilar artery aneurysms associated with fenestrations appears to offer advantages over traditional open surgical techniques.